Implementing a sustainable and efficient packaging system for e-commerce: An empirical perspective in the household sector - Jesús García-Arca; Alicia Trinidad González-Portela Garrido; Jacobo Escurís-Ouviña; J. Carlos Prado-Prado (Journal of Industrial Engineering and Management)
Purpose: The growing importance of e-commerce has negative effects on the sustainability of supply chains, highlighting the need for appropriate packaging system design. Thus, it is increasingly common to see cities where thousands of packages are delivered every day, increasing congestion and pollution, but also increasing the consumption of materials and generation of waste, because these packages are often oversized. Therefore, retailers should consider different strategies for reducing the sustainable impact of their activities. In this context, the main objective of this article is to understand, illustrate and compare the solutions adopted in the e-commerce packaging, measuring their impact on sustainability, and paying a special attention to household products.